Case Method in Teaching Pedagogical Approach: Case Method in Teaching Pedagogical Approach - Safarova, Zarnigor (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In the context of the case method involves providing insightful commentary, indicating key themes, posing relevant questions, and highlighting critical elements within the case study. This process helps to guide student understanding, stimulate thoughtful discussions, and encourage focused analysis of the presented material. This article aims to provide a comprehensive overview of the case method in teaching, exploring its foundational principles, application across diverse academic domains, and its pedagogical impact on fostering critical thinking, problem-solving, and decision-making skills.